Population of Rafflesia Patma at Leuweung Cipeucang Geopark Ciletuh Sukabumi - Ardika Eri Triana; Agus Hikmat; Sambas Basuni (Media Konservasi, 2017)
Rafflesia is a largest flower in its species in the world. The main issues which threatened this species were cause by; the destruction of therainforest as its natural fragmentation habitat and for its land conversion moreover the lack of conservation effort and understanding from thestakeholder. This plant belongs to endemic and protect species in Indonesia. This research purpose is to analyze Rafflesia patma population andecology at Leuweung Cipeucang Geopark Ciletuh Sukabumi. Purposive sampling was used to collect data in this research by using 1.000 meter plotplotwhich involve Rafflesia patma population and ecological data. The population data covering size, shape, quantity and inflorescence phase ofRafflesia patma while the ecological data covering the plant vegetation and physical habitat. 21 individual Rafflesia patma were found at LeweungCipeucang, and at the high of 196-217 m dpl Tetrastigma papilosum were located. Rafflesia patma population consists of 13% blooming flower, 9%inanimate after blooming, 26% living knop, 52% dead knop. The Highest significant index value (INP) occur in seeding level and stake on Streblusilicifolius species from Moraceae Family with 58,5% INP value at seeding level, 28% at stake level, at the tree vegetation level occur at Ficustinctoria species from Moracea family with 37,45% INP value. The highest diversity index occurs on seeding level vegetation is at 9,54.Keyword: Ciletuh Cipeucang, ekologi, populasi, Rafflesia